Thermal image, partial discharge and leakage current correlation of ceramic insulator under different contamination level - Darwison, Darwison (Asian Research Publishing Network, 2017)
This paper reports correlation on leakage current and thermograph infrared (IR) images of the ceramic outdoor insulator for the condition based monitoring purposes. In this work, laboratory pollution performance test using sodium chloride was performed according to the IEC 60507 standard with applied ac voltage from 12 kV to 18 kV. The severity level of pollution were controlled and represented by ESDD values of 0.00 to 0.25. Also, relative humidity conditions were controlled on the range between 60% to 100%. Statistical parameter of infrared images were evaluated to assess the severity level of contaminated ceramic insulator. The output IR images of the insulator were categorized as safe state, necessary maintenance and dangerous based on the level of contamination severity. The results showed that the severity of the pollution can be identified based on the analysis of infrared images, where each severity level of leakage current was correlated with a particular colour. Also, it was found that the phase difference between the leakage current to the reference voltage decreased along with the increase in the severity level of pollution.